2015
DOI: 10.1093/annonc/mdu567
|View full text |Cite
|
Sign up to set email alerts
|

Randomized phase III trial of prophylactic cranial irradiation versus observation in patients with fully resected stage IIIA–N2 nonsmall-cell lung cancer and high risk of cerebral metastases after adjuvant chemotherapy

Abstract: In patients with fully resected postoperative pathologically confirmed stage IIIA-N2 NSCLC and high risk of cerebral metastases after adjuvant chemotherapy, PCI prolongs DFS and decreases the incidence of brain metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
96
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(98 citation statements)
references
References 27 publications
0
96
1
Order By: Relevance
“…Five out of the six RCTs reported a significant decrease in BM incidence (14,15,17,18,22). A reduction in BM was seen following PCI in the Veterans Administration Lung Group (VALG) trial (6% vs. 13%; p=0.038) (17) and the MD Anderson Cancer Center (MDACC) trial (4% vs. 23%; p=0.002) (15).…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Five out of the six RCTs reported a significant decrease in BM incidence (14,15,17,18,22). A reduction in BM was seen following PCI in the Veterans Administration Lung Group (VALG) trial (6% vs. 13%; p=0.038) (17) and the MD Anderson Cancer Center (MDACC) trial (4% vs. 23%; p=0.002) (15).…”
Section: Resultsmentioning
confidence: 97%
“…All studies investigating the incidence of BM reported a decrease with the use of PCI and seven studies reported this decrease as being statistically significant (11,(14)(15)(16)(17)(18)22) (Table I). The greatest difference in the incidence rate of BM between PCI and observation was seen in the trial by Stuschke et al (11) (incidence rate of BM at 4 years 13% vs. 54%, respectively; p=0.0004).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations